2010
DOI: 10.1111/j.1365-2109.2010.02683.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction between wild fish aggregations at fish farms and fisheries activity at fishing grounds: a case study with Boops boops

Abstract: Coastal aquaculture installations concentrate large numbers of wild ¢sh species of both ecological and economic importance, including schools of bogue, Boops boops (L.), in high abundance and biomass. The aggregated species consume large quantities of the easily available pellets lost from cages. As a consequence, the physical condition of farm-associated wild ¢sh is increased and their physiology is altered. These changes may in£uence local ¢sheries as many of these aggregating species are targeted by ¢shers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 58 publications
4
61
0
1
Order By: Relevance
“…In our study, higher fat content in liver tissues was detected in F-Saithe than in U-Saithe, which were captured >25 km away from farms. Previous studies on Saithe, but also on other farm-aggregated species, revealed higher lipid levels and condition indices (i.e., Fulton's condition index, hepatosomatic index) in farm-aggregated fish compared with nonaggregated individuals (Skog et al 2003;Fernandez-Jover et al 2007, 2011bArechavala-Lopez et al 2011;Izquierdo-Gomez et al 2015). The incorporation and storage of FAs in fish tissues strongly depends on the FA profile of the diet (Sargent et al 2002).…”
Section: Discussionmentioning
confidence: 96%
“…In our study, higher fat content in liver tissues was detected in F-Saithe than in U-Saithe, which were captured >25 km away from farms. Previous studies on Saithe, but also on other farm-aggregated species, revealed higher lipid levels and condition indices (i.e., Fulton's condition index, hepatosomatic index) in farm-aggregated fish compared with nonaggregated individuals (Skog et al 2003;Fernandez-Jover et al 2007, 2011bArechavala-Lopez et al 2011;Izquierdo-Gomez et al 2015). The incorporation and storage of FAs in fish tissues strongly depends on the FA profile of the diet (Sargent et al 2002).…”
Section: Discussionmentioning
confidence: 96%
“…This concentration of fish increases the fishing pressure around the farms, with commercial and recreational fishing vessels moving around different fish farms along the same coastal area (Arechavala-Lopez et al 2011). Thus, fishing vessels attracted by fish farms could also spread C. scaura not only from one farm to another but also between coastal and offcoast locations.…”
Section: Discussionmentioning
confidence: 99%
“…Fishing near fish farms is a common practice that has been reported in Spain (Fernandez-Jover et al 2008, Arechavala-Lopez et al 2011, Croatia (Šegvić Bubić et al 2011), Greece (Machias et al 2006) and Norway (Maurstad et al 2007), and even within farms in Turkey (Akyol & Ertosluk 2010). The farms studied here are located in waters within the jurisdiction of the local government, which has not implemented any fishing restrictions in their vicinity.…”
Section: Discussionmentioning
confidence: 99%